Cardio-Oncology: Vascular and Metabolic Perspectives. Issue 13 (26th March 2019) - Campia, Umberto; Moslehi, Javid J.; Amiri-Kordestani, Laleh; Barac, Ana; Beckman, Joshua A.; Chism, David D.; Cohen, Paul; Groarke, John D.; Herrmann, Joerg; Reilly, Carolyn M.; Weintraub, Neal L.
Abstract : Cardio-oncology has organically developed as a new discipline within cardiovascular medicine as a result of the cardiac and vascular adverse sequelae of the major advances in cancer treatment. Patients with cancer and cancer survivors are at increased risk of vascular disease for a number of reasons. First, many new cancer therapies, including several targeted therapies, are associated with vascular and metabolic complications. Second, cancer itself serves as a risk factor for vascular disease, especially by increasing the risk for thromboembolic events. Finally, recent data suggest that common modifiable and genetic risk factors predispose to both malignancies and cardiovascular disease. Vascular complications in patients with cancer represent a new challenge for the clinician and a new frontier for research and investigation. Indeed, vascular sequelae of novel targeted therapies may provide insights into vascular signaling in humans. Clinically, emerging challenges are best addressed by a multidisciplinary approach in which cardiovascular medicine specialists and vascular biologists work closely with oncologists in the care of patients with cancer and cancer survivors. This novel approach realizes the goal of providing superior care through the creation of cardio-oncology consultative services and the training of a new generation of cardiovascular specialists with a broad understanding of cancer treatments.